2019
DOI: 10.1055/s-0039-3400226
|View full text |Cite
|
Sign up to set email alerts
|

LEOPARD Syndrome with PTPN11 Gene Mutation in Three Family Members Presenting with Different Phenotypes

Abstract: LEOPARD syndrome (LS) is a rare autosomal dominant disorder that is characterized by multiple lentigines and various congenital anomalies. The clinical diagnosis of LS requires molecular confirmation. The most frequently reported mutations in LS patients are in the protein tyrosine phosphatase nonreceptor type 11 gene, PTPN11. Herein, we report the cases of three family members from two generations who are affected by LS and all carry the PTPN11 mutation c.836A > G (p.Tyr279Cys), identified by next-generati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 26 publications
1
3
0
3
Order By: Relevance
“…Leopard syndrome is a rare multiple congenital anomaly with mutation in the PTPN1 gene (Alfurayh et al, 2020) (Pahwa & Sethuraman, 2012). The characteristics of the present case included in this systematic review agree with this information, with the syndrome affecting a 16-year-old boy.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Leopard syndrome is a rare multiple congenital anomaly with mutation in the PTPN1 gene (Alfurayh et al, 2020) (Pahwa & Sethuraman, 2012). The characteristics of the present case included in this systematic review agree with this information, with the syndrome affecting a 16-year-old boy.…”
Section: Discussionsupporting
confidence: 86%
“…Leopard syndrome is a rare multiple congenital anomaly with mutation in the PTPN1 gene (Alfurayh et al., 2020). Since clinical manifestations are variable, a molecular test is necessary for the diagnosis of LS.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, this is the second report with a documented PTPN11 gene mutation in Saudi Arabia, after the first one being reported by Alfurayh et al [ 3 ] A comparison of the clinical features of the other cases reported in Saudi Arabia is shown in Table 1 .…”
Section: Discussionmentioning
confidence: 86%
“…LEOPARD (OMIM #151,100), also known as neuro-cardio-cutaneous (NCFC) syndrome, is a rare autosomal dominant disease that is characterized by multisystemic disorders and typical germline PTPN11 mutations [ 2 4 , 12 , 16 ]. Approximately 85% of patients with LEOPARD syndrome harbor a missense mutation in the PTPN11 gene, two of which Tyr279Cys and Thr468 Met account for 65% of cases [ 12 ].…”
Section: Discussionmentioning
confidence: 99%